If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 4) + -2(x + -1) = -4(x + -3) + 36 Reorder the terms: 7(4 + x) + -2(x + -1) = -4(x + -3) + 36 (4 * 7 + x * 7) + -2(x + -1) = -4(x + -3) + 36 (28 + 7x) + -2(x + -1) = -4(x + -3) + 36 Reorder the terms: 28 + 7x + -2(-1 + x) = -4(x + -3) + 36 28 + 7x + (-1 * -2 + x * -2) = -4(x + -3) + 36 28 + 7x + (2 + -2x) = -4(x + -3) + 36 Reorder the terms: 28 + 2 + 7x + -2x = -4(x + -3) + 36 Combine like terms: 28 + 2 = 30 30 + 7x + -2x = -4(x + -3) + 36 Combine like terms: 7x + -2x = 5x 30 + 5x = -4(x + -3) + 36 Reorder the terms: 30 + 5x = -4(-3 + x) + 36 30 + 5x = (-3 * -4 + x * -4) + 36 30 + 5x = (12 + -4x) + 36 Reorder the terms: 30 + 5x = 12 + 36 + -4x Combine like terms: 12 + 36 = 48 30 + 5x = 48 + -4x Solving 30 + 5x = 48 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 30 + 5x + 4x = 48 + -4x + 4x Combine like terms: 5x + 4x = 9x 30 + 9x = 48 + -4x + 4x Combine like terms: -4x + 4x = 0 30 + 9x = 48 + 0 30 + 9x = 48 Add '-30' to each side of the equation. 30 + -30 + 9x = 48 + -30 Combine like terms: 30 + -30 = 0 0 + 9x = 48 + -30 9x = 48 + -30 Combine like terms: 48 + -30 = 18 9x = 18 Divide each side by '9'. x = 2 Simplifying x = 2
| 4*1-2y=2 | | 8a+7=6a+2 | | -4x+4/5=6/7 | | 5a+33=-2a+-44 | | 137-5x=22x+17 | | y=240x+720 | | 5x+5y=9x-6y | | 8+2y=1+4x | | -4=-11y | | -3x+2x=2x | | 1/9y=-8 | | (1/x)-x=(7/3) | | bxa-bx=ab | | 4(a+24)=80 | | -5/16/16/-5 | | 0.77=x/(1-(1+x))^-15 | | (A-1)bx=ab | | 4a+24=88 | | 9y-8=2y+20 | | y=3/8x-9 | | y=3/8-9 | | 6-8x=156-43x | | ((-3)/5)/(6/15) | | -7*-6x*-4x= | | 17+16+x/3=20 | | -6x*-7= | | -6x*-4x= | | -6yx-4y= | | 8(x-5)+2(7-3x)=74 | | 12(t-8)=204 | | -6x(-4x-7)= | | 17+16+x=20 |